2022
DOI: 10.1177/09603271221111440
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin cardioprotection in cyclophosphamide-induced toxicity via the modulation of inflammasome/caspase1/interleukin1β pathway

Abstract: Drug-induced cardiotoxicity is a serious adverse effect that occurs during the administration of chemotherapeutic agents such as cyclophosphamide (CYC). Therefore, there is a critical need to find cardioprotective agents to keep the heart healthy. The current study aimed to investigate the protective effect of simvastatin (SIM) against CYC-induced heart damage and evaluate different mechanisms involved in mediating this effect, including the inflammasome/caspase1/interleukin1β (IL1β) pathway and endothelial ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Similar results were obtained by other cytotoxic drugs on the myocardium as cyclophosphamide (Refaie, El-Hussieny et al 2022) or doxorubicin (Pınarlı, Turan et al 2013, Huang, Lei et al, 2022 due to the toxic effects of these drugs in addition to the associated myocardial ischemia that leads to chromosomal aberrations, cardiac cell death, and apoptosis.…”
Section: Discussionsupporting
confidence: 73%
“…Similar results were obtained by other cytotoxic drugs on the myocardium as cyclophosphamide (Refaie, El-Hussieny et al 2022) or doxorubicin (Pınarlı, Turan et al 2013, Huang, Lei et al, 2022 due to the toxic effects of these drugs in addition to the associated myocardial ischemia that leads to chromosomal aberrations, cardiac cell death, and apoptosis.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, Simvastatin is also effective against several toxins such as cyclophosphamide-induced toxicity via the modulation of inflammasome/caspase1/interleukin 1β [ 50 ], lipopolysaccharide-induced myocardial injury by up-regulating survivin that inhibits caspase-3 activation [ 51 ] and Ischemia–reperfusion-induced myocardial damage by reducing oxidative stress [ 52 ]. Considering the ability of Simvastatin to protect cardiac tissues from being damaged by toxins, it became necessary to explore its effectiveness against alcohol-induced cardiomyocyte damage and it is not surprising that the present study found that both Simvastatin concentrations (5 mg or 15 mg) significantly reduced alcohol-induced cardiomyocyte hypertrophy, cardiac fibrosis, and inflammation, whilst the administration of Simvastatin alone did not seem to be toxic to the cardiac tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Its checkpoint function makes it one of the primary organs targeted by drug toxicity (Salama et al, 2022). Hepatotoxicity of CTX is also reported by Refaie et al (2022) because it is a prodrug and so undergoes hepatic metabolism. CYP34A acts on CTX in the liver, converting it to phosphoramide mustard and acrolein (Barnett et al, 2021).…”
Section: Introductionmentioning
confidence: 99%